1972
DOI: 10.1042/cs0420209
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Changes of Haemodynamics, Renal Function, Plasma Catecholamines and Plasma Renin Concentration in Normal and Hypertensive Man

Abstract: S U M M A R Y1. In eight normal subjects, ten patients with labile hypertension, six with advanced essential hypertension and six with renovascular hypertension, plasma renin concentration, cardiac output, mean arterial pressure, clearances of creatinine and p-aminohippurate (PAH), and sodium excretion were measured before and after 30 min of 45" upright tilting. Changes in plasma adrenaline and noradrenaline concentration were measured in addition in the normal subjects, and in plasma volume in normal subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
21
1

Year Published

1976
1976
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 17 publications
(26 reference statements)
4
21
1
Order By: Relevance
“…A mean decrease in GFR of 18 and 28% in erect lordosis has been observed in patients with orthostatic proteinuria by King and Baldwin (7) and Robinson and colleagues (9) respectively. Furthermore, creatinine clearance has also been found to decrease markedly in the erect position in a series of patients with different parenchymal renal diseases (10), and in hypertensive patients during upright tilting (11).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A mean decrease in GFR of 18 and 28% in erect lordosis has been observed in patients with orthostatic proteinuria by King and Baldwin (7) and Robinson and colleagues (9) respectively. Furthermore, creatinine clearance has also been found to decrease markedly in the erect position in a series of patients with different parenchymal renal diseases (10), and in hypertensive patients during upright tilting (11).…”
Section: Discussionmentioning
confidence: 93%
“…The influence of postural changes on renal function has been studied previously by a number of workers (4)(5)(6)(7)(8)(9)(10)(11). However, it is difficult to carefully compare the results of these studies because of the different techniques and varied experimental conditions employed by these workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, several important issues can be addressed. In normal individuals, the gravitational stress of head up tilt is associated with peripheral pooling ofblood, reduction ofvenous return, and subsequent reduction of cardiac output (37,38). To protect and maintain blood pressure, head up tilt stimulates baroreceptor mechanisms that result in an increase of heart rate and systemic vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models and in humans have demonstrated abnormalities of sympathetic and parasympathetic control of heart rate in chronic congestive heart failure. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Few data are available regarding the effects of vasodilator therapy on these abnorrnalities, although this mode of therapy is widely used. '6 Vasodilator therapy could significantly alter the vasoconstriction, volume alterations and hormonal response that normally accompany the assumption of upright posture.…”
mentioning
confidence: 99%